Biological and physical controls on O2/Ar, Ar and pCO2 variability at the Western Antarctic Peninsula and in the Drake Passage. (May 2017) - Eveleth, R.; Cassar, N.; Doney, S.C.; Munro, D.R.; Sweeney, C.
Abstract: Using simultaneous sub-kilometer resolution underway measurements of surface O2 /Ar, total O2 and p CO2 from annual austral summer surveys in 2012, 2013 and 2014, we explore the impacts of biological and physical processes on the O2 and p CO2 system spatial and interannual variability at the Western Antarctic Peninsula (WAP). In the WAP, mean O2 /Ar supersaturation was (7.6±9.1)% and mean p CO2 supersaturation was (−28±22)%. We see substantial spatial variability in O2 and p CO2 including sub-mesoscale/mesoscale variability with decorrelation length scales of 4.5 km, consistent with the regional Rossby radius. This variability is embedded within onshore–offshore gradients. O2 in the LTER grid region is driven primarily by biological processes as seen by the median ratio of the magnitude of biological oxygen (O2 /Ar) to physical oxygen (Ar) supersaturation anomalies (%) relative to atmospheric equilibrium (2.6), however physical processes have a more pronounced influence in the southern onshore region of the grid where we see active sea-ice melting. Total O2 measurements should be interpreted with caution in regions of significant sea-ice formation and melt and glacial meltwater input. p CO2 undersaturation predominantly reflects biological processes in the LTER grid. In contrast we compare these results to the Drake Passage where gas supersaturations vary by smaller magnitudes and decorrelate at length scales of 12 km, in line with latitudinal changes in the regional Rossby radius. Here biological processes induce smaller O2 /Ar supersaturations (mean (0.14±1.3)%) and p CO2 undersaturations (mean (−2.8±3.9)%) than in the WAP, and pressure changes, bubble and gas exchange fluxes drive stable Ar supersaturations.